Gestural listening in and beyond the classroom - Feibush, Laura, author; Utah State University Press, publisher (Colorado State University. Libraries, 2026)
Feibush joins the conversation of those who study the rhetorical dimension of silent yet communicative behaviors of listening, analyzing not only the body language of listening but situations rhetorically through the theoretical lens of gestural listening.--Provided by publisher.
1. Looking for Listening: A Rhetorical History of Gestural Listening -- 2. Listening in the Classroom: Respect, Resistance, and Self-Regulation -- 3. Gestural Listening across Identity -- 4. Listening with Technology -- 5. Gestural Listening Currents beyond the Classroom -- Conclusion: Listening Configurations.
Keywords: English language -- Rhetoric -- Study and teaching (Higher); Listening -- Study and teaching (Higher); Gesture -- Psychological aspects -- Study and teaching (Higher); Nonverbal communication in education -- Study and teaching (Higher)